The challenge of prognostic markers in pleural mesothelioma - Imperatori, Andrea; Castiglioni, Massimo; Mortara, Lorenzo; Nardecchia, Elisa; Rotolo, Nicola (Journal of Thoracic Disease, 2013)
Malignant pleural mesothelioma (MPM) is a very aggressive tumor, highly resistant to chemo- and radio-therapy. Treatment of MPM patients is often disappointing, regardless of the modality used. Inter-individual variability of response to multimodal treatment remains a challenge and generally the MPM prognosis continues to be poor. Knowledge of predicting factors of outcome is currently insufficient; therefore, it would be highly desirable to find specific prognostic markers for MPM. Translational research projects are to be implemented.